1998
DOI: 10.1902/annals.1998.3.1.108
|View full text |Cite
|
Sign up to set email alerts
|

The Pathobiology of Periodontal Diseases May Affect Systemic Diseases: Inversion of a Paradigm

Abstract: A new paradigm for the pathobiology of periodontitis is presented, and the manner in which periodontitis may relate to susceptibility for certain systemic diseases such as cardiovascular disease and preterm labor is described. Periodontitis is caused by a small group of Gram-negative bacteria present on the tooth root surfaces as bioffilms. Lipopolysaccharide (LPS) and other substances gain access to the gingival tissues, initiate and perpetuate immunoinflammation, resulting in production of high levels of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
226
0
41

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(268 citation statements)
references
References 43 publications
(14 reference statements)
1
226
0
41
Order By: Relevance
“…These include periodontal disease (19 -21), acute necrotizing gingivitis (20,21), dental caries (21)(22)(23), herpes labialis (1,21), recurrent aphthous ulcerations (21), and impaired oral wound healing (24). The relevance of these observations may not be limited to the dental sciences, because impaired oral health is a risk factor in cardiovascular disease and respiratory infection (25)(26)(27)(28). Last but not least, saliva contains many of the antimicrobial proteins also found in other mucosal secretions (4), which makes saliva a representative model for studying secretory immunity.…”
Section: Introductionmentioning
confidence: 99%
“…These include periodontal disease (19 -21), acute necrotizing gingivitis (20,21), dental caries (21)(22)(23), herpes labialis (1,21), recurrent aphthous ulcerations (21), and impaired oral wound healing (24). The relevance of these observations may not be limited to the dental sciences, because impaired oral health is a risk factor in cardiovascular disease and respiratory infection (25)(26)(27)(28). Last but not least, saliva contains many of the antimicrobial proteins also found in other mucosal secretions (4), which makes saliva a representative model for studying secretory immunity.…”
Section: Introductionmentioning
confidence: 99%
“…In a 5-year prospective study titled "Oral Conditions and Pregnancy (OCAP)" Offenbacher et al [11], demonstrated that both antepartum maternal periodontal disease and incidence/progression of periodontal disease based on full mouth periodontal examination are associated with preterm birth and growth restriction. Regarding the potential mechanism behind this relationship is that premature birth and periodontal disease share a common pathological pathway, inflammation [12][13][14][15][16]. Pathogenesis of periodontitis involves release of inflammatory cytokines, specially IL-1B, PGE2, TNF alpha.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal health are fundamental for reducing transitory bacteremia, which may be a particular risk in susceptible patients (Siqueira & Teixeira 2001) or contribute to an aggravation in metabolic conditions like those of diabetes mellitus (Page, 1998). Furthermore, it is known that acute infections cause resistance to insulin, diminishing glucose absorption (Yki-Järvinen et al) and that the same may occur in chronic periodontal infections, which would make metabolic control of the diabetic difficult and would contribute to an increased resistance to insulin (Grossi & Genco).…”
Section: Discussionmentioning
confidence: 99%